2014
DOI: 10.9790/0853-131253944
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Of Age Estimation In Kerala Population Using Gustafson’s Formula: A Forensic Evaluation

Abstract: Gustafson's age estimation includes six age related changes of teeth. He then calculated the regression formula to estimate the age. Six criteria are level of attrition, secondary dentine deposition in pulp, changes in periodontium, root resorption, cementum apposition and root translucency. The aim of the study was to study the physiological changes of teeth according to the Gustafson's criteria and to access the age of the patient according to Gustafson's formula, Maples and Rice and to derive a new formula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
1
0
1
Order By: Relevance
“…Chandler [29] in 2013 in his study found a mean error of ±11.6 to ±13.7 years in Western Cape and John et al [30] in 2014 found the mean error of ±4.…”
Section: Discussionmentioning
confidence: 98%
“…Chandler [29] in 2013 in his study found a mean error of ±11.6 to ±13.7 years in Western Cape and John et al [30] in 2014 found the mean error of ±4.…”
Section: Discussionmentioning
confidence: 98%
“…Daha sonra çok sayıda çalışmacı tarafından Gustafson'un belirlediği kriterlerden esinlenerek oluşturulan modifiye metotlar kullanılarak dental yaş tayini çalışmaları gerçekleştirilmiştir (20)(21)(22)(23)(24)(25)(26)(27). Yapılan literatür taramasında, Gustafson metodu veya modifikasyonları kullanılarak gerçekleştirilen çalışmaların iki boyutlu görüntüleme yöntemleri olan periapikal veya panoramik radyografiler kullanılarak gerçekleştirildiği ve sağ ve sol kadranlardaki dişler arasında yaş tayini açısından farklılık olup olmadığının araştırılmadığı görülmektedir (11,26,28,29).…”
Section: Discussionunclassified